The Role of Teachers in Enhancing Students’ Learning Motivation Through Group Discussion–Based Mathematics Learning in Grade 5 At SDN 2 Cilandak - Suharyanto Soro; Nana Herdiana Abdul Rahman; Nur Widyasti Utami; Widia Utami (Global Education Journal, 2026)
This research is motivated by the low motivation of students to learn mathematics subjects at the elementary school level. Learning motivation is one of the important factors affecting the quality of mathematics learning. However, in practice, mathematics learning is still often perceived as a difficult and uninteresting subject by students, thus having an impact on low learning motivation. This study aims to describe the existence of teachers in increasing student learning motivation through mathematics learning based on group discussion activities. This study uses a case approach with data collection methods carried out through observation, interviews, and documentation. The respondents of the study are grade V teachers and grade V students of SDN 2 Cilandak. The results of the study show that (1) The existence of teachers is reflected through the role of teachers as planners, implementers, facilitators, motivators, and evaluators in mathematics learning based on group discussions; (2) Group discussion activities can create a more active, collaborative, and fun learning atmosphere, thereby encouraging optimal student involvement. The conclusion of this study is that mathematics learning based on group discussion activities can be an alternative effective learning strategy to increase student learning motivation with optimal teacher existence support.